Comparative analysis of the efficiency of algorithms fast Fourier transform in the basis systems - Белецкий, Анатолий Яковлевич; Лужецкий, Владимир Андреевич (Ukrainian Information Security Research Journal, 2017)
The article deals with the comparative analysis of the effectiveness of two classes of fast Fourier transform algorithm (FFT) in the bases of classical systems of Walsh functions and bases Walsh-like systems of the golden section features binary-power order. As a criterion of the ef-fectiveness of the FFT algorithm selected the principle of linear frequency scales connectivity FFT processor. The set of numbers from 0 to processor input channels are equidistantly arranged on a frequency axis constitutes an input frequency scale, and the set of equidistantly spaced on the frequency axis output channel numbers of the output frequency scale FFT processor. The only basis, delivering linear scales connectivity to private FFT processor is the basis of classical Walsh functions Coulee, whose analogue does not exist in the set-bases Terminals. On this basis, formulate an opinion on inappropriate use of Walsh-like-bases Terminals to perform the tasks of the spectral analysis of discrete complex exponential signals.